PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GIVING QUESTION AND GETTING ANSWER (GQGA) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 1 AMPEK NAGARI KABUPATEN AGAM - Sari, Indah Permata; Rismen, Sefna; Husna, Husna (STKIP PGRI Sumbar, 2013)
This research was motivated by the lack of understanding of studentsâ mathematical concepts and students are not accustomed to propose their ideas. This study aims to determine whether studentsâ understanding of mathematical concepts by applying active learning strategies Giving Question and Getting Answer (GQGA) type accompanied quiz is better than studentsâ understanding of mathematical concepts using conventional learning in class VIII SMP Negeri 1 Ampek Nagari Agam. This type of research is an experimental research based on the Subject with a Random design. The study population was a class VIII student SMP Negeri 1 Ampek Nagari Agam consisting of three classes. The sample was VIII1 grade students as the experimental class and VIII3 the control class. The research instrument was a quiz and final test in the form of essays. The data obtained were analyzed using t-test of the parties with the help of software MINITAB. Based on the test results obtained by the hypothesis P-value of 0.005 , then the hypothesis in this study received. It can be concluded that the studentsâ understanding of mathematical concepts by applying active learning strategies Giving Question and Getting Answer (GQGA) type quiz is better than studentsâ understanding of mathematical concepts applied on conventional learning in class VIII SMP Negeri 1 Ampek Nagari Agam.